VIRTUAL PUZZLE AS AN INTERACTIVE MODULE OF A MULTIMEDIA RESOURCE ENSURING ART COMMUNICATION OF PRIMARY SCHOOLCHILDREN IN THE PROCESS OF DISTANCE ART LEARNING - Ocheretiana, Nataliia (Theoretical and Methodical Problems of Children and Youth Education, 2022)
The article highlights the issue of using a virtual puzzle in teaching of art to primary schoolchildren of institutions in general secondary education in the conditions of a distance learning – via asynchronous and synchronous forms. The main attention is focused on the need for art teachers to transform forms and technologies of working with students and to transfer the process of art education to the virtual space due to the challenges of the pandemic and the war in Ukraine in 2022. It is noted that of using the latest multimedia technologies is reasonable as a complex of information technologies with the possibility of combining different types of data (text, sound, graphics, video, etc.) working in dialog mode and creating multimedia tools for various purposes. A virtual puzzle is considered as an interactive module available for students to use and to create a new one on various online services or platforms. Online services that have greater potential for this module to use during art education in institutions of general secondary education are Puzzle It!, Jigsawplanet and LearningApps.org. The features of using ready-made puzzles from services and constructing new ones are described according to the subject of art lessons, lesson tasks (summarization of lesson or semester material, formative types of assessment, etc.), preferences or tastes of students, levels of their development. The author concludes that the virtual puzzle as an educational and game interactive form encourages primary schoolchildren to learn about art through research, accumulate experience in active artistic activity, as well as stimulates students to communicate on art topics and promotes the development of communication skills. The value of the virtual puzzle for a teacher lies in its opportunity to encode any information, concepts of art in it, use it in individual, pair and group work, and use it in research, quests, competitions and other art activities at online lessons, or do puzzle as a task for asynchronous distance learning form. The virtual puzzle attracts students because of its similarity with a computer game. It allows them to learn new things in art in an interesting, easy and exciting way, to demonstrate their knowledge, to gain experience using it in new educational situations, to learn about art in communication with the teacher and peers that certifies the formation of students’ subject competencies and soft skills.